An approach using a low-code platform for retraining professionals to ICT - Metrôlho, J.C.M.M. (2019)
Information and Communications Technology is a growing area with a growing demand for employees. However, there is a shortage of professionals in this area and integrated strategies are required to foster the access of more people to these areas and provide training to develop the necessary skills. In this paper we present a short course that was designed to retrain unemployed people, mainly with already a higher education level in the area of the science technology engineering and math (STEM), to be Information and communications technology (ICT) professionals. After this training, trainees will have the opportunity to significantly increase the likelihood of being able to obtain employment in ICT areas. The course described involves public entities (including a higher education institution) and a private company, which is also a demonstration of synergies between academia and business. In the paper, the context that led to the appearance of the course, the fundamentals that supported the syllabus design, the partners involved, the objectives of the several subjects, the profile of the trainees and the results already achieved are described. To explain the fundamentals of the course syllabus we explain the most original features of the course regarding the usefulness of taking advantage of the abstraction allowed by the new low-code platforms, what seem to be appropriate and facilitator for retraining professionals from STEM to ICT. This approach, using a low code platform for retraining professionals to ICT, presents in our point of view, advantages over other approaches. In short, in the paper we intend to share the work done during the design and follow-up of the course, as well as the preliminary results obtained in the meantime.